Fighting procrastination for financial wellness - harness the power of inertia - Wang, Tianyang, author; Society of Actuaries, publisher (Colorado State University. Libraries, 2017)
The need to save for financial wellness is universal, yet planning for it is hard. According to a 2016 PricewaterhouseCoopers survey, 52% of employees report difficulty managing their personal finances. A majority of Americans today face a looming retirement crisis considering the fact that the median retirement account balance is only $2,500 for all working-age households and $14,500 for near-retirement households. More astoundingly, a recent Federal Reserve study reports that nearly half of Americans do not even have $400 in savings in case of an emergency.